Hubungan Kebiasaan Merokok Keluarga dan Penggunaan Parfum Ruangan dengan Keluhan Rinitis Alergi pada Anak Usia 13-14 Tahun di Kecamatan Rungkut Kota Surabaya - Muhammad Aziz Al Fakhry; Corie Indria Prasasti (Universitas Airlangga, 2023)
ABSTRACT Background: Allergic rhinitis is defined clinically as a symptom of nasal hypersensitivity triggered by a certain allergen present in the environment. The prevalence of allergic rhinitis has increased over the past 5 years. Indoor air quality is influenced by the number of pollutants according to the place, climate, culture, local ambient air, characteristics of buildings and indoor activities. Objectives: To analyze the relationship between family smoking habits and room perfume use with complaints of allergic rhinitis in children aged 13-14 years in Rungkut District, Surabaya City. Methods: This research method was quantitative research with an analytical type of observational research with a cross-sectional research design. The sample size in this study was 94 children aged 13-14 years and the sample was taken using systematic random sampling. Data collection by conducting interviews, observations and measurements directly. The test used is chi-square Results: There was a relationship between family smoking habits and complaints of allergic rhinitis in children (p = 0.000) and there was a relationship between the use of room perfume and complaints of rhinitis in children (p = 0.029). Conclusion: Family smoking habits and the use of room perfume have a significant relationship with complaints of allergic rhinitis in children. Families are encouraged to eliminate smoking and minimize the use of room perfume in order to minimize risk factors for complaints of allergic rhinitis in children.